Pengaruh Kepercayaan, Promosi Dan Kemudahan Penggunaan Terhadap Keputusan Pembelian Pada Grabfood Di Kota Batam - Sembiring, Stevanus; ., Suhardi (JURNAL ILMIAH FEASIBLE: Bisnis, Kewirausahaan dan Koperasi, 2024)
This research aims to investigate the influence of trust, promotion and ease of use on purchasing decisions at GrabFood in Batam City. This research involves consumers or GrabFood users in 2023 as a population. In this research, 100 respondents were selected as samples using the Lameshow formula method with withdrawal based on purposive sampling. Data analysis was carried out using multiple linear regression, with data quality testing, classical assumption testing, influence testing, and hypothesis testing. Findings in multiple linear regression analysis show that trust has an influence of 33.2% on purchasing decisions. Promotions have an influence of 29.2% on purchasing decisions. Ease of use has an influence of 23.1% on purchasing decisions. The findings were measured using coefficient of determination analysis (R2), which showed that trust, promotion and ease of use together explained 65.4% of the variation in purchasing decisions. Furthermore, the results of the t test and F test show that trust, promotion and ease of use have a positive and significant effect on purchasing decisions at GrabFood in Batam City.